Studi Kelayakan Investasi Batching Plant menggunakan Fly Ash sebagai Pengganti Semen di Kota Palembang - Dwi Utama, Hakim Abdurrahim; Susanti, Betty; Saloma, Saloma (Jurnal Rekayasa Mesin, 2024)
Cement processing increases CO2 pollution by up to 6%, giving rise to innovation in using fly ash because it can be used as an additive material for good quality concrete. Concrete production using a batching plant requires large investment costs. This research aims to analyze the feasibility of financial investment to build a batching plant that processes concrete mixed with fly ash and compare it with conventional concrete without fly ash in Palembang City. The study shows the NPV>0, IRR>9%, and BCR>1, which means these two investments are feasible. However, the payback period for conventional concrete is 3 years while concrete with fly ash is 3.5 years. BEP for conventional concrete and fly ash concrete reached the break-even point in the 8th year. In the 10th year of fly ash concrete production, there was a significant surplus. The environmental aspect shows that concrete waste using fly ash is safe because it can reduce cement use by up to 55%. The research results show that adding fly ash reduces raw material costs. This investment is declared feasible from a financial aspect because it has the potential to obtain benefits.